Can the Kyoto Protocol to the United Nations Framework Convention on Climate Change achieve its ultimate objective? - Dalrymple, James (Institute of Marine and Environmental Law, 2023)
Hardly a day goes by without reading, in the national and international media, about new evidence of catastrophic climate change, be it droughts, floods, fires, storms or wildlife extinction. But are we to blame? Are anthropogenic (human-induced) interferences with the climate system causing. climate change? Are the emissions from factories and cars changing the relationship between us and nature? Will we destroy the basic conditions that. have allowed life to thrive on Earth? These are the questions which have caused so much soul-searching amongst people over the past few decades with regard to climate change. It is not within the scope of this paper to prove or disprove the existence of dangerous anthropogenic climate change. What is important from an international environmental law perspective is whether or not the nations of the world believe there is a climate change problem, and if they do what rules must be put in place to deal with the problem. That first significant step towards legally recognising that there is a climate change problem was taken in 1992 with the signing of the United Nations Framework Convention on Climate Change (referred to in this paper as the UNFCCC. or the Convention). This Convention was a direct consequence of scientific evidence, produced by the Intergovernmental Panel on Climate Change (IPCC), showing the devastating effects of dangerous anthropogenic greenhouse gases caught in the atmosphere. A second major step towards legally binding commitments to reducing greenhouse gas emissions was made, after intensive negotiations, in Kyoto, Japan, with the signing of a Protocol to the Framework Convention. The Kyoto Protocol (the Protocol) signed in 1997, is significant because it introduces for the first time, legally binding obligations on developed countries to reduce their emissions of greenhouse gasses. In 1995 the IPCC released a report which concluded that the climate may have already started responding to past emissions. It recommended that, in order to stabilise atmospheric concentrations of greenhouse gases at 1990 levels, it would be necessary to reduce current anthropogenic emissions by 60%. This figure went far beyond the reductions to which even the most environmentally progressive Parties were prepared to commit. So, can the Protocol to the UNFCCC achieve its ultimate objective, which is to stabilise greenhouse gas concentrations in the atmosphere at a level that will prevent dangerous anthropogenic interference with the climate system?